2008
DOI: 10.1038/sc.2008.100
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of physical interventions for people with spinal cord injuries: a systematic review

Abstract: Study design: Systematic review. Objectives: To provide a quantitative analysis of all randomized controlled trials designed to determine the effectiveness of physical interventions for people with spinal cord injury (SCI). Setting: Sydney, Australia. Methods: A search was conducted for randomized controlled trials involving physical interventions for people with SCI. Two reviewers independently rated methodological quality using the PEDro scale and extracted key findings from the trials. Results: Four thousan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 43 publications
0
66
0
Order By: Relevance
“…4 The results indicate a statistically significant increase in voluntary strength, although there is uncertainty as to whether the size of the treatment effect is clinically important (the 95% CI spanned the sufficiently important difference of 8 Nm). The effects of ES superimposed on PRT on stimulated strength, stimulated endurance and voluntary endurance were equivocal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The results indicate a statistically significant increase in voluntary strength, although there is uncertainty as to whether the size of the treatment effect is clinically important (the 95% CI spanned the sufficiently important difference of 8 Nm). The effects of ES superimposed on PRT on stimulated strength, stimulated endurance and voluntary endurance were equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…there is no direct evidence from clinical trials to suggest that voluntary strength is increased by superimposing ES on PRT 4,9,10 or by superimposing ES on any type of voluntary exercise in people with muscle paresis. [11][12][13] Therefore, the primary purpose of this trial was to determine the clinical effectiveness of ES superimposed on PRT for increasing voluntary strength in the paretic quadriceps muscles of people with SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also beneficial for psychological well-being, participation in the community, and quality of life. 4,5 Previous studies have shown that preserved muscle strength, as assessed using the International Standards for Neurological Classification of Spinal Cord Injuries (ISNCSCI) neurological assessment, is highly correlated with ambulation ability. 6,7 Ambulatory capacity is defined as the degree of independence in walking, both at home and outdoors in the community.…”
Section: Introductionmentioning
confidence: 99%
“…This may be a result of the increased number of people living with incomplete SCIs [1]. Consequently, rehabilitation therapies have altered, to address activity limitations that patients may experience, to increase participation in the community and to improve patients' overall quality of life [2]. One of the primary goals of thebeing [5].…”
Section: Introductionmentioning
confidence: 99%